Enhancing Islamic Education Institutions’ Quality to Capture Public Interest (A Multi-Site Study at MTs Darul Hikmah and MTs Mamba’ul Ulum Tulungagung) - Indrioko, Erwin (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The advancement of modern science has had a considerable impact on Islamic education, necessitating a shift in focus from its traditional role as a moral foundation to one of competition with public education. This research project examines strategies for enhancing the quality of Islamic education and attracting public interest. It employs a multi-site study of two Islamic educational institutions: The two Islamic educational institutions under consideration are MTs Darul Hikmah Tulungagung and MTs Mamba’ul Ulum Tulungagung. A qualitative approach was employed to collect data through in-depth interviews, participatory observation, and documentation. Informants included school heads, deputies, teachers, and student guardians. The findings indicate that both institutions implement total quality management strategies, with a particular focus on enhancing the competence of educators, improving facilities, optimising educational management, refining learning processes, developing graduate competencies, enhancing evaluations, and securing adequate funding. Furthermore, they proactively disseminate information about their institution through social and mass media in order to influence public perception. The aforementioned continuous quality improvement efforts have resulted in a notable increase in the number of student applicants on an annual basis, thereby demonstrating the efficacy of the strategies employed in enhancing the institution’s appeal and competitiveness.